Halal Tourism: The Issue of Qibla Direction at Several Tourist Attractions in West Sumatra Province - Hendri; Sairon (AL - AFAQ : Jurnal Ilmu Falak dan Astronomi, 2025)
This article aims to analyze the accuracy of the qibla direction in prayer rooms located in several tourist attractions in West Sumatra, where deviations in the qibla direction certainly raise doubts about the validity of prayers for visitors to these tourist attractions. Therefore, this article will explore three issues: the problem of qibla direction in prayer rooms in several tourist attractions in West Sumatra, how visitors respond to the problem of qibla direction at prayer sites in several tourist attractions in West Sumatra, and how accurate the qibla direction is at prayer sites in several tourist attractions in West Sumatra. The research method used is a mixed method with data sources obtained through observation, interviews, and documentation, as well as descriptive analysis. The findings in this article show that the problem of qibla direction in places of worship at several tourist attractions in West Sumatra can generally be divided into three categories. These categories are technical problems, non-technical problems, and fiqh problems. Visitors' responses to the problem of qibla direction can also be divided into proactive responses, adaptive responses, and passive responses. The accuracy of the qibla direction in places of worship in several tourist areas in West Sumatra shows that 10% of places of worship in several tourist areas have a qibla direction that is classified as very accurate. In addition, 42% fall into the accurate category, 32% into the fairly accurate category, and 16%.